Some methods of fish capture in Marikina River. - Ignacio, Sixto S. (College of Fisheries, University of the Philippines, 1952)
Marikina River is located at the main road 8 miles NE of Pasig. Geographically 14 degree39' latitude and 121 06' longitude. It is situated along the town of Montalban, Sasn Matei and as far as the town of Pasig, which location makes it fisheries of considerable economic importance. This river has sandy bottom and some parts are muddy. In this river are found different species of fish almost all of which are edible and found in large scale. The inhabitants of the town located along or close to the rivers derive their means of livelihood mostly from fishing. Population increases from year to year which has corresponding increase in the demand of fresh fish. To satisfy this needs, fisherman modify their gears and use new ones to suit the needs of the situation that in order to catch more usher, We have now, which in our town various methods of fish capture, some of these methods are already obsolete and effective enough to supply the demand of the people.